Populism and ‘People’: Precarities and Polarizations as a Challenge and Task for a Public Theology - Sinner, Rudolf von (International journal of public theology, 2021)
Abstract Two main elements pervade the argument. First, we argue that both ‘populism” and ‘the people’ are precarious concepts that can neither easily be defined, nor easily be claimed by any representative. We hold this to be true both in political and in theological terms, empirically referring to the civil and the religious population and their construction as ‘a people’, respectively. Second, in view of a common disregard for the people, namely as plebs, we reaffirm the importance of participatory popular subjects as a necessary part of both the political system and Christian communities. This bibliographical and conceptual essay contextualizes and explains the precariousness of realities and concepts, then analyses the concepts of populism and ‘people’. It seeks to deepen the discussion of populism by means of dialogue with Ernesto Laclau and Chantal Mouffe, and then through a theological reflection by way of a public theology.